Block Propagation in Blockchain-Based 6G Network: From a Communication Perspective - Wang, Yisong; Zhang, Xuefei; Wang, Xiaochen; Cui, Qimei; Tao, Xiaofeng (2022 14th International Conference on Wireless Communications and Signal Processing (WCSP), 2022)
The 6th generation (6G) communication network in the future will be participated by multi-parties (e.g., cellular network, satellite network, vehicular network, etc.). Integrating blockchain into 6G can provide a credible decentralized environment between untrusted parties. Most existing works assume that the block propagation time is ignorable as it is insignificant compared with the block mining time in consensus. However, the block propagation time is no longer negligible in such a wireless and heterogeneous 6G network. To be specific, the deterministic communication in the wired network changes to the opportunistic communication resulting from the moving nodes (e.g., vehicles and satellites) that adopt wireless communication. In this work, we study block propagation in the 6G network. Specifically, we establish the analytical model with the discrete-time Markov chain from the microscopic view to portray the block propagation process in three specific cases. On this basis, we present a hybrid-communication-modes-based block propagation mechanism (HCM) to optimize the propagation time. Finally, the simulation results demonstrate the effectiveness of the proposed mechanism.